Development of a virtual environment for motion analysis of tennis service returns - Saito, K.; Masai, K.; Sugiura, Y.; Kimura, T. (MMSports'18: Proceedings of the 1st International Workshop on Multimedia Content Analysis in Sports, 2018)
In sports performance analysis, it is important to understand differences between experts and novices in order to train novices in an efficient manner. To understand these differences within the game of tennis, we developed a virtual environment to analyze the responses of experts and novices to services. By capturing actual service motions of an expert, it is possible to reproduce virtualized services in the environment. We did experiments on types and courses of services. As a result, we found differences between experts and novices in preparation, leg movement, take-back returns, and degree of spine twist.